A Tale of Two Houses: Opera Houses in Cairo and Cape Town. (March 2021) - Somma, Donato
Abstract: This article considers the parallel histories of the opera houses in Cairo, Egypt and Cape Town, South Africa. Their respective stories reflect common and divergent experiences of the colonial and postcolonial and the emergent national and nationalist identities at the terminal cities of Africa. Considered separately from the content performed on their stages, the article traces the significance of the buildings as part of their cities. In each city the opera house has been destroyed and rebuilt, under new regimes with new purposes. The discursive value of opera houses is considered more broadly, with evidence presented for the houses as functionaries of the 'operatic state' or impresarialist institutions. Who is welcomed in and courted at the opera house is investigated as part of the phenomenon of a nominally public space with conventionalised issues of access.